2022
DOI: 10.1093/ejcts/ezac013
|View full text |Cite
|
Sign up to set email alerts
|

Ross procedure provides survival benefit over mechanical valve in adults: a propensity-matched nationwide analysis

Abstract: OBJECTIVES The choice of optimal surgical treatment for young and middle-aged adults with aortic valve disease remains a challenge. Mechanical aortic valve replacement (mAVR) is generally preferred despite promising recent outcomes of the Ross procedure. Our goal was to compare the strategies at a nationwide level. METHODS This study was a retrospective analysis of prospectively recorded data from the National Registry of Car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 30 publications
1
17
0
5
Order By: Relevance
“…In addition, 21 articles were excluded with the following reasons: n=10: no comparison or control groups; n=4: neither randomized nor PSM; n=3: pediatric patients aged <16 years; n=2: review article; n=1: no outcomes of interest reported; and n=1: trial protocol. Ten articles met the inclusion criteria and were assessed for the systematic review and the meta‐analysis 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 29 (Figure S1 ). Of those, 2 were RCTs 10 , 29 and 8 were PSM studies, 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 which enrolled a total of 4812 patients who received the Ross procedure (n=1991), M‐AVR (n=2019), or B‐AVR (n=802).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, 21 articles were excluded with the following reasons: n=10: no comparison or control groups; n=4: neither randomized nor PSM; n=3: pediatric patients aged <16 years; n=2: review article; n=1: no outcomes of interest reported; and n=1: trial protocol. Ten articles met the inclusion criteria and were assessed for the systematic review and the meta‐analysis 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 29 (Figure S1 ). Of those, 2 were RCTs 10 , 29 and 8 were PSM studies, 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 which enrolled a total of 4812 patients who received the Ross procedure (n=1991), M‐AVR (n=2019), or B‐AVR (n=802).…”
Section: Resultsmentioning
confidence: 99%
“…Ten articles met the inclusion criteria and were assessed for the systematic review and the meta‐analysis 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 29 (Figure S1 ). Of those, 2 were RCTs 10 , 29 and 8 were PSM studies, 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 which enrolled a total of 4812 patients who received the Ross procedure (n=1991), M‐AVR (n=2019), or B‐AVR (n=802).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of MACCE was extremely low and comparable in both cohorts. According to the latest evidence, the Ross procedure is the only valve substitute to offer the patients survival comparable with age- and sex-matched general population ( 23 25 ). Despite very favorable long-term outcomes in the first two decades, the most recent insight from the German Ross Registry indicates a trend toward impairment of autograft and homograft function in the third decade accompanied by a decline of survival of Ross patients ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…There has been a resurgence of interest in the Ross procedure for this cohort with increasing evidence suggesting that Ross patients may confer superior long-term outcomes compared to conventional aortic valve replacement (AVR) [ 1 ]. In this issue of the Journal , Gofus et al [ 2 ] evaluated mid-term outcomes of the Ross procedure compared to a propensity-matched cohort of mechanical AVR. The authors reported a lower all-cause mortality in the Ross cohort even after adjusting for only cardiac and valve-related deaths with no difference in risk of aortic reoperation.…”
mentioning
confidence: 99%